Optimization of poultry offal and extender levels for cost-effective chicken sausage production - Rahmana, M H; Hossain, A; Arac, T; Islam, M (Bangladesh Journal of Animal Science, 2025)
The research was carried out to examine the use of consumable broiler and spent hen offal in raw chicken meat to prepare chicken meat sausages. For preparing chicken meat sausages, along with edible poultry parts such as skin, liver, gizzard, and heart were used at 15%, 20% and 25% levels whereas extenders used at 25%, 30% and 35% respectively. These sausages were tested for quality and sensory characteristics. The chicken meat sausages with 15% consumable offal and 25% extenders had demonstrated significantly (p<0.05) greater folding test value, lower frying loss, acceptable pH and shrinkage value, higher cooking yield, and acceptable mean sensory taste ratings compared to the recipes that included edible offal at 20% and 25% and extenders at 30% and 35% respectively. The chicken meat sausages formulated with any of these offal and extenders levels were acceptable in terms of sensory qualities. However, the sausages with 15% edible offal and 25% extenders had better physicochemical and sensory attributes than other formulations. The study shows, the use of offal and extenders not only improves organoleptic, physicochemical and sensory values but also presents immense opportunity for cost reduction in poultry meat processing. Bangladesh Journal of Animal Science 54 (2): 44 - 53, 2025